Differential temporal dynamics of axial and appendicular ataxia in SCA3 - Maas, Roderick; Teerenstra, Steven; Lima, Manuela; Pires, Paula; Pereira de Almeida, Luís; Gaalen, Judith van; Timmann, Dagmar; Infante, Jon; Onyike, Chiadi; Bushara, Khalaf; Jacobi, Heike; Reetz, Kathrin; et al. (Movement disorders, 2022)
Background Disease severity in spinocerebellar ataxia type 3 (SCA3) is commonly defined by the Scale for the Assessment and Rating of Ataxia (SARA) sum score, but little is known about the contributions and progression patterns of individual items. Objectives To investigate the temporal dynamics of SARA item scores in SCA3 patients and evaluate if clinical and demographic factors are differentially associated with evolution of axial and appendicular ataxia. Methods In a prospective, multinational cohort study involving 11 European and 2 US sites, SARA scores were determined longitudinally in 223 SCA3 patients with a follow-up assessment after 1 year. Results An increase in SARA score from 10 to 20 points was mainly driven by axial and speech items, with a markedly smaller contribution of appendicular items. Finger chase and nose-finger test scores not only showed the lowest variability at baseline, but also the least deterioration at follow-up. Compared with the full set of SARA items, omission of both tests would result in lower sample size requirements for therapeutic trials. Sex was associated with change in SARA sum score and appendicular, but not axial, subscore, with a significantly faster progression in men. Despite considerable interindividual variability, the average annual progression rate of SARA score was approximately three times higher in subjects with a disease duration over 10 years than in those within 10 years from onset. Conclusion Our findings provide evidence for a difference in temporal dynamics between axial and appendicular ataxia in SCA3 patients, which will help inform the design of clinical trials and development of new (etiology-specific) outcome measures. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.